2009
DOI: 10.1016/j.conengprac.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A modelling methodology for natural dam-river network systems

Abstract: a b s t r a c tAn approach for modelling a natural dam-river network system is proposed in this paper. Generally, the relationships among the variables of a natural dam-river network system are complex and difficult to describe. In this paper, some simple relationships among the water levels measured at a limited number of points of the network system are presented in such a way that a simple model is achieved. The model is identified and validated with the real time operational data. An example is given and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Furthermore, the relationship assessment of variables from reservoirs and rivers natural system [54]; A Bayesian network to manage gates to avoid floods, helpful on decision making about which maneuvers has to be performed [55]; The analysis of water temperature variation due to dams structure revealed that gates operation does not have a great influence on water temperature, and that this variable is mainly influenced by climate conditions and hydrologic variables [56]; A Fuzzy Logic for the reservoirs operation system on hydropower plants, taking into account energy cost uncertainties on gate water flow [21].…”
Section: Systematic Literature Review On Economic and Environmental Amentioning
confidence: 99%
“…Furthermore, the relationship assessment of variables from reservoirs and rivers natural system [54]; A Bayesian network to manage gates to avoid floods, helpful on decision making about which maneuvers has to be performed [55]; The analysis of water temperature variation due to dams structure revealed that gates operation does not have a great influence on water temperature, and that this variable is mainly influenced by climate conditions and hydrologic variables [56]; A Fuzzy Logic for the reservoirs operation system on hydropower plants, taking into account energy cost uncertainties on gate water flow [21].…”
Section: Systematic Literature Review On Economic and Environmental Amentioning
confidence: 99%